21st Century Challenges Confronting Women Entrepreneurs in Southwest Nigeria - Aladejebi, Olufemi (Archives of Business Research, 2020)
Women Entrepreneurs play a significant role in the global economy in this 21st Century. The purpose of this study is to examine the specific challenges faced by women entrepreneurs in the southwestern states of Nigeria. Data were collected from businesses owned by women who reside within the six state capitals of Southwestern states of Nigeria. The cities are Lagos, Abeokuta, Ibadan, Oshogbo, Akure, and Ado-Ekiti. Similar big cities within each state were surveyed to increase the number of respondents for state capitals where a small number of questionnaires were retrieved. Out of Seven hundred and twenty (720) questionnaires distributed, Five hundred and two (502) questionnaires were viable using the SPSS package. The questionnaire contained two sections. Section 1 for general information. Section 2 contained questions relating to motivational factors and the challenges faced by these women entrepreneurs, which, in their opinion, constitutes barriers to the successes of their businesses. The main challenges facing women entrepreneurs today in South West Nigeria are lack of adequate training, access to start-up capital, and poor family support.